Differential optogenetic activation of the auditory midbrain in freely moving behaving mice - Rogalla, Meike M.; Seibert, Adina; Sleeboom, Jana M.; Hildebrandt, K. Jannis (Frontiers in Systems Neuroscience, 2023)
In patients with severe auditory impairment, partial hearing restoration can be achieved by sensory prostheses for the electrical stimulation of the central nervous system. However, these state-of-the-art approaches suffer from limited spectral resolution: electrical field spread depends on the impedance of the surrounding medium, impeding spatially focused electrical stimulation in neural tissue. To overcome these limitations, optogenetic activation could be applied in such prostheses to achieve enhanced resolution through precise and differential stimulation of nearby neuronal ensembles. Previous experiments have provided a first proof for behavioral detectability of optogenetic activation in the rodent auditory system, but little is known about the generation of complex and behaviorally relevant sensory patterns involving differential activation.In this study, we developed an optogenetic implant to excite two spatially separated points along the tonotopy of the murine inferior colliculus (ICc). Using a reward-based operant Go/No-Go paradigm, we show that differential optogenetic activation of a sub-cortical sensory pathway is possible and efficient. We demonstrate how animals which were previously trained in a frequency discrimination paradigm a) rapidly respond to either sound or optogenetic stimulation, b) generally detect optogenetic stimulation of two different neuronal ensembles, and c) discriminate between them. Our results demonstrate that optogenetic excitatory stimulation at different points of the ICc tonotopy elicits a stable response behavior over time periods of several months. With this study, we provide the first proof of principle for sub-cortical differential stimulation of sensory systems using complex artificial cues in freely moving animals.